Architecture and key technologies of the space-air-ground integrated network empowered by integrated sensing, computing and communication - LI Lanlan (Dianxin kexue)
With the rapid development of 6G communication technology, integrated sensing, computing, and communication (ISCC) has become a key driving force in the evolution of space-air-ground integrated network. Starting from the core concept of ISCC, its critical role in space-air-ground integrated network was discussed, and a multi-level management and orchestration network architecture empowered by ISCC was proposed. Key technologies of this architecture were analyzed. Finally, the current challenges faced in this field were summarized, and future development trends were prospected, aiming to provide valuable reference and insights for the construction of space-air-ground integrated network in the 6G era.